Northern News - North America, Arctic Institute of (ARCTIC, 1952)
The news items include: 1) a summary of round table conference concerning Eskimo affairs that was held in Ottawa on May 19-20, 1952 (reprinted from Arctic Circular, v. 5, no. 4, 1952, p. 41-43); 2) information on the Canadian ice distribution survey by J. Keith Fraser (reprinted from Arctic Circular, v. 5, no. 5, 1952, p. 56); 3) a summary of two articles written by Provst Aage Bugge (an obituary of Provst C.W. Schultz-Lorentzen and a book review of a novel, "Kateketen Johannes", by Karl Heilmann) that were published in pamphlet no. 79 of Meddelelser om Den grønlandske Kirkesag; and 4) a notice that the Shorey Book Store of Seattle has issued a catalogue of their books on Alaska and the Arctic.